To assess the Influence of Selected Community Based Factors on Girls’ Participation Rate in Public Day Secondary Schools in Naivasha Sub-County, Kenya. - Gatere, Janet Waithira; Kiumi, Prof. J. Kanjogu; Ngugi, Dr. Margaret (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the influence of selected community based factors on girls’ participation rate in public day secondary schools in Naivasha Sub-County, Kenya. Ex-post facto research design was used in the study. A total of 130 respondents (constituting 26 principals and 104 teachers) from 26 schools were randomly sampled for the study. All the targeted respondents participated in the study giving a response rate of 100%. Simple random sampling technique was used to sample the respondents for the study. Data was collected through a self-administered questionnaire where two sets of questionnaires were developed for data collection; one for principals and the other for class teachers. Descriptive statistics such as means, percentages and frequencies were used to analyze the data while inferential statistics such as simple regression analysis was used to determine the predictive power of community factors on girls’ participation in school. The study found that three community-level risk factors that had the most negative effect on girls’ participation in public day secondary schools in the study area including: negative peer influence in the community, high incidences of teenage pregnancies and poverty in the community. Drawing from the computed R2 value (R2 = .406), the study revealed that the selected community factors were lowering the rate of girls participation in public day secondary schools by almost 41%. The study concluded that prevalence of the three community level factors such as: high incidence of teenage pregnancies and poverty had great influence on girls’ participation and progression in public day secondary schools in the study area. It was recommended that school, family and community partnerships would be appropriate in minimizing the effect of community level factor on girls’ participation in schools.